2017
DOI: 10.2147/ott.s149716
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the cardiac safety between cetuximab and panitumumab as single therapy in Chinese chemotherapy-refractory mCRC

Abstract: ObjectiveThe cardiac safety of cetuximab and panitumumab, particularly as single agents, has not been investigated extensively. This trial was designed to specifically evaluate the cardiac safety of cetuximab and panitumumab as single therapy in Chinese chemotherapy-refractory metastatic colorectal cancer (mCRC) patients.Patients and methodsSixty-one patients received cetuximab at an initial dose of 400 mg/m2 intravenously over 120 minutes on day 1 (week 1), followed by a maintenance dose of 250 mg/m2 intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Cetuximab and panitumumab have comparable CV toxicity profiles [30]. Tang et al (2017) reviewed the assessment of the cardiac safety between cetuximab and panitumumab as single therapies in Chinese chemotherapy-refractory mCRC and concluded that cetuximab and panitumumab caused cardiotoxicity [31]. In the cetuximab group, there were still three patients with unspecified ST changes and three patients with QTc prolongation at 10 months after therapy, but in the panitumamab group, there were only two patients with nonspecific ST changes and four patients with QTc prolongation.…”
Section: Cetuximab and Panitumumabmentioning
confidence: 99%
See 1 more Smart Citation
“…Cetuximab and panitumumab have comparable CV toxicity profiles [30]. Tang et al (2017) reviewed the assessment of the cardiac safety between cetuximab and panitumumab as single therapies in Chinese chemotherapy-refractory mCRC and concluded that cetuximab and panitumumab caused cardiotoxicity [31]. In the cetuximab group, there were still three patients with unspecified ST changes and three patients with QTc prolongation at 10 months after therapy, but in the panitumamab group, there were only two patients with nonspecific ST changes and four patients with QTc prolongation.…”
Section: Cetuximab and Panitumumabmentioning
confidence: 99%
“…In the cetuximab group, there were still three patients with unspecified ST changes and three patients with QTc prolongation at 10 months after therapy, but in the panitumamab group, there were only two patients with nonspecific ST changes and four patients with QTc prolongation. The majority of the specific ST alteration and QTc prolongation brought on by cetuximab and panitumumab therapy may be reversible according to this result, however, the persistence of these abnormalities requires more investigation and care [31].…”
Section: Cetuximab and Panitumumabmentioning
confidence: 99%
“…Panitumumab has been reported to cause hypomagnesemia, hypokalemia, dehydration, hypotension, hypertension and VTEs (58). Cetuximab and panitumumab have a similar CV toxicity profile, with the most common cardiac events requiring treatment being palpitations/arrhythmias (25.8%), chest pain (8.1%), arrhythmias (4.8%) (59) and dyspnea (60).…”
Section: Cetuximab and Panitumumabmentioning
confidence: 99%